Optical Coherence Tomography Findings in Idiopathic Macular Holes - Lynn L. Huang; David H. Levinson; Jonathan P. Levine; Umar Mian; Irena Tsui (Journal of Ophthalmology)
Purpose. To describe the characteristics of idiopathic macular holes (MH) on optical coherence tomography (OCT) and correlate OCT with clinical assessment. Design. Cross-sectional chart review and OCT assessment. Participants. Sixty-seven eyes with a clinically diagnosed idiopathic MH with available OCT data. Methods. A retrospective chart review and OCT assessment. Results. Based on OCT grading, 40 eyes had a full-thickness macular hole (FTMH) and 21 eyes had a lamellar macular hole (LMH). Clinical exam and OCT assessment agreed in 53 (87%) eyes when assessing the extent of MH. Six eyes (14.6%) in the FTMH group, and 3 eyes in the LMH group (14.3%) had persistent vitreomacular traction. Thirty-seven eyes (92.5%) in the FTMH group and 11 eyes (52.4%) in the LMH group had associated intraretinal cysts. Two eyes (5.0%) in the FTMH group and zero eyes in the LMH group had subretinal fluid. Intraretinal cysts were found to be more frequently associated with FTMH than with LMH (P<0.001). Conclusion. This paper described OCT findings in a group of patients with clinically diagnosed MH. A high level of correlation between clinical assessment and OCT findings of LMH and FTMH was observed, and intraretinal cysts were often present in FTMH.